When I lived and died in the city, I had nothing, nothing to fear: : the musical silence in cities in 2020 - Silva, Paulo Celso (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2022)
February 2020. European cities are beginning to feel the first signs of the pandemic. What seemed to be restricted to Asian cities, spreads rapidly and in a few weeks around the world. With unprepared citizens and cities taking refuge in homes, it is the only way to contain the even greater spread of the Covid19 virus. Silence takes over the streets, squares, avenues that, lonely, some are taken over by animals. This work, a mixture of personal experience, contribution of musicians with their testimonies, theories, rehearses a reflection of urban everyday life and its sound. He appropriates Albert Plà's song, ¿Os acordàis? for a poetic reflection of the moment lived and a graphic reinterpretation of the song.